Analysis of online buying behaviour for women face cleanser product: a study for hada nature brand of pt. Salica beauty indonesia. - Situmeang, Marhara; Titus, Amol (The Indonesian Journal of Business Administration, 2019)
Abstract: The final thesis proposes to analyze the Indonesian beauty care sector specifically face cleanser product for women. This is one of the fastest growing sectors in Indonesia recording 2012-2017 Compound Annual Growth Rate of 13.3% in retail market. The objective is also to understand the success factors in this sector with specific reference to consumer behavior and the growing popularity of online channel. This thesis applies conceptual learning on Consumer Decision Making Process, Marketing Strategy, and Market Research. After undertaking comprehensive analysis of the industry, players, and trends in Indonesia this thesis also proposes to test the application of findings with specific live example. This relates to Salica Beauty Indonesia which is Japanese company that is trying to gain market share in the high-end face cleanser category through its Hada Nature product. The thesis has provided an opportunity to conduct various types of analysis and research which includes industry, competition, survey, interviews, academic literature review, and application of research findings to generate practical solution. The result from this thesis has shown that face cleanser high-end consumers utilize mixed of digital channels as source of awareness, evaluating brand choice, and channel to purchase. They also specifically refer to several names of social media figure which are perceived having expertise in advising brands of skin care product. Aside of digital channel, the existence offline store is still important for high-end consumers as this channel offers more complete shopping experience. Key words: beauty industry, face cleanser, high-end consumer, marketing strategy, digital channel, offline store